Genetic variability, character association and path analysis in Brassica rapa L. Genotypes - Naznin, S; Kawochar, MA; Sultana, S; Bhuiyan, MSR (Bangladesh Journal of Agricultural Research, 2015)
Thirty three genotypes of Brassica rapa L. were evaluated in order to find out their inter-genotypic variability; character association and path coefficient of seed yield/plant and its component characters. BARI sarisha-6 x TORI-7 S-45 showed best result in terms of early maturity (75 days) and higher seed yield/plant (5.28g) than check varieties. The character, plant height, was highly influenced by the environment whereas, all other characters influenced the least. Number of secondary branches/plant showed the highest phenotypic and genotypic coefficient of variation. Moreover, number of siliquae/plant, number of secondary branches/plant and number of primary branches/plant showed high heritability (93.16%, 75.69% and 68.03%, respectively) couple with high genetic advance in percent of mean (37.74%, 73.55% and 26.82%, successively). The seed yield/plant showed significant positive correlation with number of siliquae/plant (rg = 0.7011**, rp = 0.5684**), number of primary branches/plant (rg = 0.5611**, rp = 0.4016*) and number of secondary branches/plant (rg = 0.5160**, rp = 0.4098*) revealing that selection based on these traits would be judicious. Path analysis showed that the number of siliquae/plant (0.4679), number of primary branches/plant (0.2823) and number of secondary branches/plant (0.0092) were the most important contributors to seed yield/plant. The results indicated that number of siliquae/plant, number of primary branches/plant and number of secondary branches/plant can be used as selection criteria to increase seed yield/plant in rapeseed. Bangladesh J. Agril. Res. 40(2): 305-323 June 2015